Effectiveness of the South African expanded program of immunization against hepatitis B in children infected with human immunodeficiency virus‐1 living in a resource‐limited setting of Kwazulu‐Natal. Issue 1 (24th June 2016) - Beghin, Jean‐Christophe; Ruelle, Jean; Sokal, Etienne; Bachy, Antoine; Krishna, Malini; Hall, Leslie; Goubau, Patrick; Van der Linden, Dimitri
Abstract : Prevalence of Human‐Immunodeficiency‐Virus/Hepatitis‐B‐virus (HIV/HBV) coinfection and HBV vaccination response in children are unknown in Kwazulu‐Natal. This study included 183 HIV‐infected and 108 HIV‐uninfected children aged between 5 and 15 years screened for HBV infection and vaccination. HBV infection occurred in 2.1% and 0% of HIV‐infected and uninfected children respectively. Serological response to immunization was shown in 15.8% and 61.1% of HIV‐infected and uninfected children, respectively ( P < 0.001). Even if prevalence of HBV infection was low in these cohorts, HIV‐infected children will stay at risk of infection if the vaccine schedule is not adapted. J. Med. Virol. 89:182–185, 2017 . © 2016 Wiley Periodicals, Inc.